Bill Mauldin papers - Mauldin, Bill, 1921-2003.; Mauldin, Bill, 1921-2003.; Mauldin, Bill, 1921-2003.; Mauldin, Bill, 1921-2003.; Mauldin, Bill, 1921-2003.
Correspondence, speeches, writings, family papers, and other papers regarding Mauldin's career as a cartoonist, his work on behalf of the American Veterans Committee, and his interest in civil aviation. Subjects include World War II; the coronation of Elizabeth II, Queen of Great Britain, in 1952; and Mauldin's 1956 congressional campaign in New York State. Includes drafts of his books, Up Front (1945), Back Home (1947), A Sort of a Saga (1949), and Bill Mauldin in Korea (1952). Correspondents include Art Buchwald, Milton Arthur Caniff, Daniel Robert Fitzpatrick, E.J. Kahn, Will Lang, Reg Manning, Herbert Mitgang, A.S. Mike Monroney, Pat Oliphant, Maxwell E. Perkins, Ernie Pyle, William Lindsay White, the Wide World Lecture Bureau, and Mauldin family members, especially Mauldin's wife, Natalie Mauldin.
Library of Congress Prints and Photographs Division.
Cartoonist. Full name: William Henry Mauldin.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Buchwald, Art -- Correspondence; Caniff, Milton Arthur, -- 1907-1988 -- Correspondence; Elizabeth -- II, -- Queen of Great Britain, -- 1926-; Fitzpatrick, Daniel Robert, -- 1891-1969 -- Correspondence; Kahn, E. J. -- 1916- -- Correspondence; Lang, Will -- 1914-1968 -- Correspondence; Manning, Reg, -- 1905-1986 -- Correspondence; Mauldin, Natalie, -- 1924-1971 -- Correspondence; Mitgang, Herbert -- Correspondence; Monroney, A. S. Mike -- 1902-1980 -- Correspondence; Oliphant, Pat, -- 1935- -- Correspondence; Perkins, Maxwell E. -- 1884-1947 -- Correspondence; Pyle, Ernie, -- 1900-1945 -- Correspondence; White, William Lindsay, -- 1900-1973 -- Correspondence; Mauldin family; Mauldin family -- Correspondence; United States. -- Army -- Military life; American Veterans Committee; Wide World Lecture Bureau -- Correspondence; Aeronautics, Commercial; American wit and humor, Pictorial; Caricatures and cartoons; Korean War, 1950-1953 -- Caricatures and cartoons; Political campaigns -- New York (State); Political cartoons; Soldiers -- Caricatures and cartoons; Veterans -- United States -- Societies, etc; World War, 1939-1945.; World War, 1939-1945 -- Caricatures and cartoons; New York (State) -- Politics and government -- 1951-; United States -- Politics and government -- 20th century; Cartoonists